A Case of Radiation-Induced Multifocal Laryngeal Angiosarcoma Presenting as a Diagnostic Dilemma. (13th August 2012) - Dowdall, Jayme R.; Opfermann, Krisha J.; Kim, Harold; Lin, Ho-Sheng
Abstract : Head and neck sarcomas are relatively rare tumors, with angiosarcomas representing a small subset. Angiosarcoma is a malignant endothelial neoplasm characterized by atypical, multilayered, or solid endothelial proliferation with vasoformative architecture. The global incidence of irradiation-associated sarcoma is estimated as between 0.03% and 0.08%. Here we reported the case of an elderly woman previously treated with radiation more than 20 years ago for an unknown primary of head and neck. This interesting case presented as a diagnostic challenge, and multiple biopsies were required to eventually establish the diagnosis of laryngeal angiosarcoma. We additionally have confirmation from our prior radiation records that the patient did, in fact, receive a substantial dose of radiation to the site previously. To our knowledge, this case represents the first report of a documented radiation-induced multifocal laryngeal angiosarcoma.